ETHICAL PERSPECTIVE AND THE MAPPING OF NORM IN CORRUPTION ACT - Siti Zulaekhah (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Corruptive behavior is a despicable act and unacceptable ethically by any nation, including the country Indonesia. As a very theological country (theological based), Indonesia also has a stand against all forms of corruption acts. Through Corruption Act in 1971, 1999 and 2001 following preventive countermeasures be a guideline or reference in law enforcement. This paper aims to examine from the perspective of ethical norms and map of corruption in Law norms above. Setelah mapped, then compared to the possibilities of irregularities against the norms can be studied rationalizations. The study then followed up with an analysis of each norm on every law so the clash of ethical choices and the prevention of possible violations of norms can be explained. This study combines juridical-philosophical and normative juridical approach on the text of Law Corruption has ever been and is still in force in Indonesia. Keywords: ethical perspective, mapping the norm, corruption